Perancangan Perabot Modular Pameran Karya Mahasiswa Program Studi Desain Interior Universitas Kristen Petra Di Surabaya - Jesica Aprilliana (Intra, 2017)
Interior Design of Petra Christian University Student's Products Exhibition has the complexity of display product needs that must be fulfilled by the supporting furniture exhibition in order to be able to display the product with interesting and maximum. The furniture must have a proper, functional and practical value because the exhibition must be done with a short preparation for only few days event and it must  be able to fulfill the needs of various products. Based on the Kembel design method and using pragmatic and typological technique, turn out an exhibition furniture using a modular system with knock-down andn adjustable construction that can be arranged according to the needs of the product for vertically and horizontally display.